The Interaction of αB-Crystallin with Mature α-Synuclein Amyloid Fibrils Inhibits Their Elongation - Waudby, Christopher A. (The Biophysical Society, 2010)
αB-Crystallin is a small heat-shock protein (sHsp) that is colocalized with α-synuclein (αSyn) in Lewy bodies—the pathological hallmarks of Parkinson's disease—and is an inhibitor of αSyn amyloid fibril formation in an ATP-independent manner in vitro. We have investigated the mechanism underlying the inhibitory action of sHsps, and here we establish, by means of a variety of biophysical techniques including immunogold labeling and nuclear magnetic resonance spectroscopy, that αB-crystallin interacts with αSyn, binding along the length of mature amyloid fibrils. By measurement of seeded fibril elongation kinetics, both in solution and on a surface using a quartz crystal microbalance, this binding is shown to strongly inhibit further growth of the fibrils. The binding is also demonstrated to shift the monomer-fibril equilibrium in favor of dissociation. We believe that this mechanism, by which a sHsp interacts with mature amyloid fibrils, could represent an additional and potentially generic means by which at least some chaperones protect against amyloid aggregation and limit the onset of misfolding diseases.